Impact of technology and storage on fatty acids profile in dairy products - Laučienė, Lina (Array, 2019)
In the present study fatty acid (FA) composition in four main groups of dairy products was determined to investigate their development during processing and storage. Fresh cheese, sour cream, butter, and ultra-high temperature (UHT) milk representing differences in technological approach were chosen for the study. Fatty acids methyl esters (FAME) were quantified using a gas chromatograph (GC) equipped with a mass spectrometer (MS) and a capillary column SP-2560. The concentrations and profile of FA in final products were primarily dependent on the FA content of raw milk for UHT milk and fresh cheese production or in the raw cream for sour cream and butter. The shelf life had a significant impact (P<0.05) only in UHT milk and butter, whereby unsaturated fatty acids (UFA) and polyunsaturated fatty acids (PUFA) decreased significantly in UHT milk, while PUFA decreased significantly in butter.